Microbial Small RNAs – The Missing Link in the Nitrogen Cycle? - Moeller, Sophie; Payá, Gloria; Bonete, María-José; Gates, Andrew J.; Richardson, David J.; Esclapez, Julia; Rowley, Gary (Frontiers in Environmental Science, 2021)
Non-coding small RNAs (sRNAs) regulate a wide range of physiological processes in microorganisms that allow them to rapidly respond to changes in environmental conditions. sRNAs have predominantly been studied in a few model organisms, however it is becoming increasingly clear that sRNAs play a crucial role in environmentally relevant pathways. Several sRNAs have been shown to control important enzymatic processes within the nitrogen cycle and many more have been identified in model nitrogen cycling organisms that remain to be characterized. Alongside these studies meta-transcriptomic data indicates both known and putative sRNA are expressed in microbial communities and are potentially linked to changes in environmental processes in these habitats. This review describes the current picture of the function of regulatory sRNAs in the nitrogen cycle. Anthropogenic influences have led to a shift in the nitrogen cycle resulting in an increase in microbial emissions of the potent greenhouse gas nitrous oxide (N2O) into the atmosphere. As the genetic, physiological, and environmental factors regulating the microbial processes responsible for the production and consumption of N2O are not fully understood, this represents a critical knowledge gap in the development of future mitigation strategies.